EVALUATION OF PROSPECTS OF INTEGRATED DEVELOPMENT OF GEOTHERMAL RESOURCES OF THE NORTH CAUCASUS REGION - A. B. Alkhasov; D. A. Аlkhasova; A. Sh. Ramazanov (Юг России: экология, развитие)
The aim is to assess the prospects for the integrated development of geothermal resources in the North Caucasus region.Methods. Technological solutions are proposed for integrated development of hightemperature hydrogeothermal resources of the North Caucasus region. The evaluation of the effectiveness of the proposed technologies was carried out with the use of physico-mathematical, thermodynamic and optimization methods of calculation and physico-chemical experimental studies.Findings. Were estimated the prospects of complex processing of highly parametrical geothermal resources of the Eastern Ciscaucasian artesian basin (ECAB) with conversion of thermal energy into electric power in a binary GeoPP and subsequent extraction of dissolved chemical compounds. The most promising areas for the development of such resources were indicated. In connection with the exacerbated environmental problems, it was shown the need for the firstpriority integrated development of associated high-mineralized brines of the South Sukhokum group of gas-oil wells in North Dagestan. At present, associated brines with a radioactive background exceeding permissible standards are discharged to surface filtration fields; technological solutions for their decontamination and integrated development were proposed.Conclusions. The comprehensive development of high-temperature hydrogeothermal brines is a new direction in geothermal energy, which will significantly increase the production of hydrogeothermal resources and develop the geothermal industry at a higher level with the implementation of energy-efficient advanced technologies. Large-scale development of brines will solve significant problems of energy supply in the region and import substitution, fully meeting Russia's needs for food and technical salt and other rare elements.